Effect of the Hydroalcoholic Extract from the Leafy Stems of Waltheria indica L. (Malvaceae) on Acetylcholine and Barium Chloride-Induced Contractions on Isolated Rat Tracheal Tissue - Yabré Zakaline; Boly Rainatou; Nitiéma Mathieu; Belemnaba Lazare; Youl Noëla Hoho Estelle; Guissou Innocent Pierre; Ouédraogo Sylvin (Tehran University of Medical Sciences, 2023)
A previous study has reported the interesting relaxant effect of the hydroalcoholic extract from Waltheria indica L. (Malvaceae) leafy stems, a plant with several therapeutic uses. The present study aimed to investigate the preventive effect of this plant using an ex vivo model of the rat trachea. Two agonists, acetylcholine (10-6 - 1.5×10-5 M) and barium chloride (10-5- 10-1 M) were used to induce contractions. The preventive effect was assessed on rat tracheal rings pretreated with hydroalcoholic extract (1.92 mg/mL), glibenclamide, atropine, and papaverine, all at 10 µM. Acetylcholine and barium chloride provoke contractions in a concentration-dependent manner, with a maximum contractile response of 3.953 ± 0.692 g and 2.999 ± 0.326 g, respectively. The EC50 values were 3.711 ± 0.823 µM and 9.502 ± 12.354 mM, respectively, for acetylcholine- and barium chloride-induced contraction. Glibenclamide caused a rightward shift of the acetylcholine-response curve, followed by a reduction of the maximum contraction (from 3.953 ± 0.692 g to 3. 116 ± 0.244 g). The hydroalcoholic extract, atropine, papaverine, and their combinations induced a complete suppression of the contractile response to acetylcholine (p < 0.0001) and barium chloride (p < 0.0001). The hydroalcoholic extract exhibited a potent relaxant effect comparable to that of atropine and papaverine. It can be concluded that the hydroalcoholic extract of W. indica can potently prevent acetylcholine-and barium chloride-induced contractions. The possible mechanisms by which the extract exerts its relaxant effect may involve the blockade of muscarinic receptors, the inhibition of phosphodiesterase activity, and/or the calcium channel.